5y*2y-3=

Simple and best practice solution for 5y*2y-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y*2y-3= equation:


Simplifying
5y * 2y + -3 = 0

Reorder the terms for easier multiplication:
5 * 2y * y + -3 = 0

Multiply 5 * 2
10y * y + -3 = 0

Multiply y * y
10y2 + -3 = 0

Reorder the terms:
-3 + 10y2 = 0

Solving
-3 + 10y2 = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 10y2 = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 10y2 = 0 + 3
10y2 = 0 + 3

Combine like terms: 0 + 3 = 3
10y2 = 3

Divide each side by '10'.
y2 = 0.3

Simplifying
y2 = 0.3

Take the square root of each side:
y = {-0.547722558, 0.547722558}

See similar equations:

| x^2+sqrt(25-x^2)=7 | | 2(x+1)+3x+6=4 | | 15x-7=-2 | | t^2+4t+3=0 | | 28=2x+2 | | 3lnx^6-2lnx^2=14 | | 3ln(x^6)-2ln(x^2)=14 | | 3x-9x+5x-7x= | | cos^2x-sen^2x=0 | | 0.025p-2=0.15(p-5) | | 2.1d+18=216(d+8) | | z*8+(3-i)*z*4-3*i=0 | | 5v+3=7 | | 2q-4+8q=yq-8+3q | | 3b-(1-2b)= | | 3.5x+12=5.25x | | lg(5x-2)=lg(2-5x) | | 3b+(1-2b)= | | 5+(3b-2)= | | 8x+15y=34 | | y=9x^2-12x+4 | | 9w=5850 | | 6x+5y=7.58 | | s=-16t^2*64t+160 | | 9(7x+8)+3(x+7)=0 | | 5b^5-1280b=0 | | 9x^2+10=-96 | | -5(3x-7)=-9x | | -10x-20y+31=0 | | (x+5)dy=ydx | | (17b-8)-4(4b+3)=-7 | | 2x-3y+z= |

Equations solver categories